TRADISI MA’NENE SEBAGAI WARISAN BUDAYA ETNIS TORAJA - Rudy Gunawan; Merina Merina (Universitas Sultan Ageng Tirtayasa, 2018)
The purpose of this research is to know: (1) Ma'nene Tradition process (2) Efforts made to maintain Ma'nene Tradition (3) Ma'nene tradition becomes a cultural value of Toraja society. The research was conducted in Kete'kesu Village, Londa, Bori Parinding. The study population is Tana Toraja society which is considered to be the Toraja customs. Informants are determined by non-probability sampling. Type of research is descriptive-qualitative. The results of this study reveal that tradition has a long series of ritual processes and requires a very large cost. Nevertheless, the Toraja people still think that this tradition should continue to be done because it has a purpose and a positive meaning. The Ma'Nene ritual begins with family members coming to Patane to retrieve dead bodies of corpses and then be cleansed and cleaned by replacing new clothes. After that the body was re-entered to Patane. The procession closes with the gathering of family members at the Tongkonan traditional house to worship together. Ma'nene tradition has a uniqueness and deep meaning, that is reflects the importance of the relationship between family members uninterrupted despite being separated by death. In addition, this ritual is also used to introduce young family members with their ancestors.